Medium and large carnivores in areas under low impact forest management in the arc of deforestation, Cujubim, Rondônia (Research, Society and Development, 2022)
The objective of this work was to estimate the richness, relative abundance and composition of the fauna of medium and large carnivores that occur on the Manoa farm, Cujubim/RO, and to correlate it with the forest regeneration phase in areas exploited by the activity of sustainable management of low impact. For data collection, the camera trapping method was used and the study took place from September-December 2020 and June-September 2021, in three sample areas: Absolute Reserve, considered as a Control area; an area explored between 2011-2012 (R10); and an area explored between 2001-2003 (R20). An effort of 2,606 traps/day was carried out, in which 232 independent records were obtained and a total richness of nine species of medium and large carnivores distributed in four families. Of the total number of species recorded, six of these had shared occurrence among the three sample areas of the study, indicating a high similarity in the faunal composition. The total relative abundance was 0.09 independent records/total sampling effort and did not differ significantly between areas. The results obtained indicate that the sustainable forest management employed in the farm area, at first sight, does not negatively impact the community of medium and large carnivores, since the species composition and abundance was similar between the sampled areas. Furthermore, the detection of rare and/or vulnerable species, such as Atelocynus microtis, Leopardus wiedii, Panthera onca and Puma concolor is a good indicator of environmental quality.